In-silico model development and validation of the L5-S1 spinal unit. Issue 1 (31st December 2023) - Vinyas,; Bhat, Subraya Krishna; Adhikari, Raviraja; Bhat N, Shyamasunder
Abstract: The L5-S1 segment of the spine is highly susceptible to injury, frequently causing low back pain. The segment has gained a lot of scientific interest, leading to many experimental works that can be found describing its biomechanical characteristics. But, there is a lack of work focusing on its computational studies, which can significantly aid its further studies. In the current study, a subject-specific single-segment finite element model of the L5-S1 unit was developed from a T2-mapped MRI scan. This study is mainly intended to probe the requirements for modelling the annulus of the disc and also attempts to understand the role of ligaments exclusive to the L5-S1 spinal unit to establish its validated finite element model. The annulus was represented by two different forms of hyperelastic material models (isotropic and anisotropic) for which the constants were determined from experimental data found in the literature. Their ability to impart the required characteristic was tested for the finite element model to mimic the experimental responses during sagittal and lateral moment loads. A comparison of results with the two material models is also discussed for other valuable parameters like contact pressure at the facets, maximum von-Mises stresses in the vertebrae, ligament strains, and midplane Tresca shear stresses of the annulus. The anisotropic Gasser-Ogden-Holzapfel (GOH) model was observed to deliver a response that consistently showed good compliance with the experimental response and hence, it is recommended for the computational studies of this segment.